SP10.1.6 Benefit of Two week colorectal cancer referrals of patients who had colonic imaging within the last 5 years: do they improve the colorectal cancer outcome?. (28th October 2021) - Bavikatte prasannakumar, A; Nathan, C; Kundrapu, K; Dennis, H; Athisayaraj, T.W; Sebastian, B
Abstract: Purpose: There has been a significant rise in the number of colorectal rapid access referrals. These referral results in additional demand for hospital services as well as delays assessment and management of other patients. We analyzed the outcome of colorectal fast tract clinic re- referrals on bowel cancer outcome in patients with recent colonic imaging. Methods: We retrospectively analyzed 1000 consecutive colorectal rapid access pathway referrals in 2019.Patients with complete colonic imaging within the preceding 5 years were included. We assessed their clinical outcome and colonic imaging when performed. Results: In total, 82 (8.2%) patients out of 1000 met the selection criteria. Among these 12 patients (14%) did not need any further colonic investigations. A further 12 patients (14%) were already on the colorectal surveillance program, including a patient with recently diagnosed rectal cancer. Hence 24 patients (29.2%) referral was not indicated. 58 patients had further colonic imaging in the form of colonoscopy or virtual colonoscopy following clinic consultation. 32 (55.17%) of them had normal colonic imaging. 14 patients (24.1%) were identified with colorectal polyps with only one identified as tubular adenoma. The remaining 12 patients had non neoplastic pathology. Conclusion: No new significant colorectal pathology was identified in this group of patients. We suggest that symptomatic patients who had complete colonic imaging within 5 years be referred to routine colorectal clinic in order to make the colorectal rapid access referral pathway more effective especially during these unprecedented times.